Bibliometric Insight into Financial Sustainability Publication Trends - Kustina, Ketut Tanti; Wiksuana, I Gusti Bagus; Wiagustini, Ni Luh; Rahyuda, Henny (Universitas Mercu Buana, 2025)
Objectives: This study addresses the fragmented literature on financial sustainability by reviewing research conducted over the past five years. The objective is to bridge the knowledge gap by compiling an annotated bibliography of recent financial sustainability publications, focusing on the developments from 2018 to 2023. The paper identifies key topics and emerging research trends in this field.Methodology: The research employs bibliometric analysis and VOSviewer to analyze data from the Scopus database. It aims to identify four distinct research clusters related to financial sustainability by examining recent publications. The study also assesses the research methods used in the literature, including archival, experimental, and survey methods.Findings: The bibliometric analysis reveals four distinct research clusters that have emerged in the past decade. These clusters include topics such as co-creation, digitization of cultural heritage, financial management in the digital era, international digital platforms, ethical issues, organizational forms, social innovation, work integration social enterprises (WISE), cryptocurrencies, and financial regulation. The study also highlights the predominance of archival, experimental, and survey research methods over the past six years.Conclusion: This research provides a comprehensive overview of the evolving landscape of financial sustainability, offering valuable insights for students and academics. It summarizes key trends, methodologies, and emerging topics in financial sustainability research, contributing to a better understanding of the field and guiding future studies.